Las macrodestrezas en el aprendizaje del área de ciencias naturales de los estudiantes del quinto año de educación general básica, de la escuela Gral. Juan Lavalle, parroquia Lizarzaburu, cantón Riobamba, provincia de Chimborazo, período 2015-2016. - Puma Miñarcaja, Rosa Elena (2016)
The topic called: The macrodestrezas learning area Natural Sciences students in the fifth year of basic general education, school Juan Lavalle, the Lizarzaburu Parish, Riobamba Canton, Chimborazo Province, period 2015-2016 was developed with the purpose of deducting macrodestrezas involved in the teaching-learning process of Natural Sciences, in view curricular Updating and Strengthening of Basic General Education 2010 states that in the process of building knowledge in curriculum design is aimed at development of a logical, critical and creative thinking, through the implementation of educational objectives that are evident in the plan and treatment skills and knowledge. The curriculum proposes the implementation of activities drawn from situations and problems of life and the use of participatory learning methods to help students achieve performance achievements proposed by the output profile of the General Basic Education. This means being able to: observe, analyze, compare, sort, rasterize and plot the essential and secondary ideas interrelated, seeking common aspects, logical relationships and generalizations of ideas. Reflect, evaluate, criticize and argue about concepts, facts and study processes. Explore and produce new and different solutions to problems from different levels of thought. The research design used was experimental and not reach it framed in explicativo- descriptive methods used was the inductive and deductive. The technique was used for data collection was the survey for teachers and observation, children, where the achievements are evidence The results obtained show that partially applied the update Curricular given that the content is prioritized , the content is evaluated, is not taken into account macrodestrezas which constitute general guidelines to achieve skills with performance criteria, which are targets of the Upgrade Curricular and must be evidenced in the quality standards for that reason schedules proposed constitute support elements for the development of skills and consequently macrodestrezas with performance criteria.